The assessment of teachers’ knowledge and schools’readiness about food allergy and anaphylaxis in a Northwest city of Turkey (Annals of Medical Research, 2021)
Aim: To investigate teachers’ knowledge and preparedness of schools about food allergy and anaphylaxis in elementary schools in Edirne city.Material and Methods: The study was performed as a cross sectional survey study. Questionnaires were answered by 560 teachers, all of them were working in 35 public elementary schools in Edirne. In addition to questions concerning food allergies, teachers were asked about their attitudes in the case of a life-threatening food-induced allergic reaction. The presence of a nurse or other trained personnel, an action plan for management of anaphylaxis, and/or epinephrine availability and use in these schools in the case of such a reaction were also evaluated.Results: The vast majority of teachers (97.3%) reported they had not been informed about food allergies, and only 19.1% stated that “shock” may be related to a food allergy situation. Only 4 schools (11.4%) employed a nurse. Examination of school drugs cabinets revealed no epinephrine in any school, and none of the students were found to carry epinephrine autoinjectors. Furthermore, none of the schools had an emergency action plan related to food-induced allergic reactions. Conclusion: The current study revealed an urgent need to inform elementary school teachers of Edirne about food allergies and their treatment and to improve access to emergency treatments and action plans.
Keywords: Food allergy; school-age child; anaphylaxis; epinephrine; allergen avoidance; teachers; knowledge; readiness.